2020
DOI: 10.1038/s41598-020-60524-2
|View full text |Cite
|
Sign up to set email alerts
|

Application of latent class analysis in diagnosis of graft-versus-host disease by serum markers after allogeneic haematopoietic stem cell transplantation

Abstract: 2 for a composite test is as the same as a diagnostic test. For choosing optimal cutoff point, the Youden index which mentioned before, was used for the combinations. Afterward, the cSensitivity and cSpecificity were selected. For the models, the convergence of the MCMC chains for all the LCMs (with and without covariate adjustment) was assessed using autocorrelation plots. Furthermore, the convergence was obtained by running one chain with 35,000 iterations with lag 45. The first 17,000 iterations were discar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Studies have shown that low levels of LDH and high levels of serum cyclosporine reduce the likelihood of aGvHD [ 51 ]. In some previous studies, this variable has been presented as one of the important predictors [ 10 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that low levels of LDH and high levels of serum cyclosporine reduce the likelihood of aGvHD [ 51 ]. In some previous studies, this variable has been presented as one of the important predictors [ 10 , 52 ].…”
Section: Discussionmentioning
confidence: 99%